Hamsters make terrible roommates - Klein, Cheryl B., 1978- (Dial Books for Young Readers, 2022)
"Henry is desperate for a little peace and quiet from his extremely chatty roommate Marvin, and after Henry finally loses his cool, these hamsters must find ways to compromise and live together"--